Novel 2,6,9-Trisubstituted Purines as Potent CDK Inhibitors Alleviating Trastuzumab-Resistance of HER2-Positive Breast Cancers - Ratnakar Reddy Kuchukulla; Injeoung Hwang; Sang Won Park; Sojeong Moon; Suhn Hyung Kim; Sumin Kim; Hwan Won Chung; Mi-Jung Ji; Hyun-Mee Park; Gu Kong; Wooyoung Hur (MDPI AG, 2022)
HER2-positive (HER2+) breast cancer is defined by HER2 oncogene amplification on chromosome 17q12 and accounts for 15-20% population of breast-cancer patients. Therapeutic anti-HER2 antibody such as trastuzumab is used as the first-line therapy for HER2-positive breast cancers. However, more than 50% of the patients respond poorly to trastuzumab, illustrating that novel therapy is warranted to overcome the resistance. We previously reported that in the majority of HER2+ breast-cancer patients, CDK12 is co-amplified on 17q12 and involved in developing tumors and trastuzumab resistance, proposing CDK12 as a potential drug target for HER2+ breast cancers. Here, we designed and synthesized novel 2,6,9-trisubstituted purines as potent CDK12 inhibitors showing strong, equipotent antiproliferative activity against trastuzumab-sensitive HER2+ SK-Br3 cells and trastuzumab-resistant HER2+ HCC1954 cells (GI50 values < 50 nM) both of which express a high level of CDK12. Two potent analogue 30d and 30e at 40, 200 nM greatly downregulated the levels of cyclinK and Pol II p-CTD (Ser2), as well as the expression of CDK12 downstream genes (IRS1 and WNT1) in a dose-dependent manner. We also observed structure-property relationship for a subset of potent analogues, and found that 30e is highly stable in liver microsomes with lack of CYP inhibition. In addition, 30d exhibited a synergy with trastuzumab in the both cells, suggesting that our inhibitors could be applied to alleviate trastuzumab-resistance of HER2+ breast cancers and escalate the efficacy of trastuzumab as well. Our study may provide insight into developing a novel therapy for HER2+ breast cancers.